2014
DOI: 10.1039/c3ob42196a
|View full text |Cite
|
Sign up to set email alerts
|

Palladium catalyzed acetoxylation of benzylic C–H bonds using a bidentate picolinamide directing group

Abstract: A general palladium catalyzed acetoxylation of benzylic C-H bonds has been developed. Picolinamides serve as an excellent directing group for the C-H activation of benzylic methyls. A wide range of 2-amino benzyl alcohol analogues were synthesized in good yields. The products demonstrated broad synthetic utilities toward various benzo-fused heterocycles. Mechanistic studies revealed the key rate-limiting C-H insertion step, which could be affected by the substitution pattern of the parent arene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 44 publications
0
13
0
2
Order By: Relevance
“…According to Rumpf,42 the tensile strength of aggregates depends mainly on the particle size of the filler, and it is increased with decreasing particle diameter. Cheng 43 proposed a different relationship, suggesting a strong dependence between the strength of aggregates and the bulk density of the filler. According to Cheng, 43 the tensile strength of the aggregates should become higher with increasing filler bulk density.…”
Section: Resultsmentioning
confidence: 99%
“…According to Rumpf,42 the tensile strength of aggregates depends mainly on the particle size of the filler, and it is increased with decreasing particle diameter. Cheng 43 proposed a different relationship, suggesting a strong dependence between the strength of aggregates and the bulk density of the filler. According to Cheng, 43 the tensile strength of the aggregates should become higher with increasing filler bulk density.…”
Section: Resultsmentioning
confidence: 99%
“…The picolinoyl group could be cleaved after hydrolysis by NaOH at 50 °C, affording aminobenzyl alcohols such as 141 , important intermediates in the synthesis of oxazines and quinolones (Scheme ) . This paper was followed by kinetic studies by Huang et al They showed that each structural feature that forced the methyl group into close proximity to the metal, such as substituents at the 3‐, 5‐ and 6‐positions, preventing rotation around the aryl–N bond, resulted in the fast palladation of C–H bond in the rate‐limiting step. Efforts directed towards activation of secondary benzylic and aliphatic bonds proceed through in‐plane reductive elimination, resulting in the cyclized products.…”
Section: Intermolecular Acyloxylationmentioning
confidence: 99%
“…Use of the Pd(OAc) 2 /PhI(OAc) 2 / AcOH system led to mixtures of the corresponding four-membered azetidines and acetates, the cyclization/acetoxylation ratios depending on the substitution on the N-side [Equations (87) and (88)]. [97] Selectivity towards acetoxylation was subsequently improved by addition of salts, especially Li 2 CO 3 , in a mixed AcOH/xylene solvent system [Equation (90)]. [97] Selectivity towards acetoxylation was subsequently improved by addition of salts, especially Li 2 CO 3 , in a mixed AcOH/xylene solvent system [Equation (90)].…”
Section: N-sidementioning
confidence: 99%
“…tions (99), [96] (100), [108] (101), [108] and (102) [97] ]. The low yield obtained from N- (2,6-dimethylphenyl)picolinamide [Equation (101)] was attributed to steric hindrance.…”
Section: N-sidementioning
confidence: 99%
See 1 more Smart Citation